Cost Accounting and Product Costing: Trend of Research and Possibilities for Improvements - Mackevičius, Jonas (Ekonomika, 2004)
Product costing is essential part of the accounting system under existing competitive market economy conditions. It is essential because cost accounting and product pricing covers complex of all accounting works that directly related with accounting of raw materials, payroll expenses, current and non-current assets, currency and other technical and economical indexes.However, consideration for the cost accounting and product costing in Lithuania is insufficient. Cost accounting system does not exist in most enterprises while cost index is calculated only to fill in financial statements [D. Zinkevičienė, 1997, p. 4].It is necessary to emphasize important historical fact that cost accounting and product costing problems had been analyzed more than 20 years in certain economy and industry fields in Lithuania (since 1964 till 1985). Current scientific theses were maintained through this period: E. Kunevičius “Problems of cost accounting and product costing improvement in the industry of textile (by the example of Lithuanian TSR enterprises)” (1968), Jankaitienė “Cost accounting and product costing improvement (by the example of Lithuanian TSR enterprises of furniture industry)” (1971). V. Konstantinavičius “Problems of construction installing works expenses and product costing improvements (by the example of Lithuanian TSR ministry of construction organization)” (1971), G. Savoniakienė “Cost accounting and product costing improvements (by the example of Lithuanian TSR enterprises of sewing industry)” (1972), L. Krivka “Cost accounting and product costing improvement (by the example of enterprises of local industry)” (1973), J. Listavičius “Cost accounting and analyze improvement according to internal self-supporting circumstances (by the example of Lithuanian TSR collective farms main industry fields)” (1974), A. Sadeckas “Cost accounting and product costing improvement (by the example of Lithuanian TSR enterprises of knitted fabrics industry)” (1974), D. Mačernienė “Cost accounting and product costing improvement in the industry of instruments (by the example of Lithuanian enterprises)” (1975), E. Kunevičius “Cost accounting improvement in the industry of cotton (by the example of Lithuanian TSR enterprises)” (1976). A Valys “Cost accounting and product costing improvement in the industry of milk cattle-breeding (by the example of of Lithuanian TSR collective farms in district of Radviliškis)” (1977), L. Buikas “Production costs management accounting and control improvement (by the example of Lithuanian TSR enterprises of instruments)” (1981), J. Žaptorius “Cost accounting improvement (by the example of Lithuanian enterprises of repair of agricultural maintenance committee)” (1985), N. Stončiuvienė “Production cost accounting and its strategical control improvement in close soil market-gardening)” (1985). Problems of broader accounting, economical analyze, self-supporting and planing were investigated in the other scientists dissertations (J. Mackevičius (1966), V. Mikutis (1968). V. Bružauskas (1970), K. Pučinskas (1970), Z. Gaidienė (1972), V. Lubauskas (1980), G. Kalčinskas (1982). G. Gipienė (1983), I. Toliatienė (1983), D. Žilinskaitė (1985), G. Černius (1987), L Gaižauskas (1987) and other).Deep analyze of cost accounting and product costing problems was suspended after the restoration of Lithuanian independence. It was thought that price of the products was determined by the market in tbe market economy therefore calculation of costs was inexpedient However, practice of many countries has shown that result of enterprise activity is settled by the cost of production, that exactness of its calculation provides information which helps to decide which sort of production to produce [K. Valužis, 2001, p. 176]. Increasing influence of cost accounting on management system leads to solve many uncertain problems, for example, what expenses should be included into the costs of production, what indications should be used for classification of costs, what is the objects and unit for calculation in different industry fields and manufactures. how to choose the method of cost accounting and product costing properly, how to prepare budgets, to determine cost centres and to evaluate their efficiency. etc.Goal of research - to clear up the main trends of cost accounting and product costing investigations at the present stage of accounting development in Lithuania.Object or research - cost accounting and product costing as the main element of accounting system.Methods of research - systematic, comparative. method of literature source analyze. detailing and summarizing, marking out the prior and significant fields.Main trends of investigation of cost accounting and product were formulated: 1) determination of connection between cost accounting and product costing; 2) classification of cost accounting and product costing methods; 3) formation of budgets; 4) determination of cost centres. These questions are at a great importance for accounting system foundation in Lithuania and have theoretical and practical sense.Having analyzed connection between cost accounting and product costing problems it was determined that: 1) cost accounting and product costing is general process of cost investigation, estimation, summarize, control, evaluation and determination of cost of all production and specific unit. Cost accounting and product costing helps to solve many problems - to achieve economy, to use all kinds of cost rationally, to disclose internal reserves of production, to decrease cost of production, to increase profitableness and etc.; 2) cost accounting and product costing are two different stages of management accounting, but are connected strongly: cost of production is determined upon cost accounting data, at the same time product costing makes direct influence on cost accounting. Product costing can be treated as continuation of the cost accounting. Therefore separation of cost accounting from product costing is conditional, more theoretical question.Analyze of cost accounting and product costing methods classification problem has determined that this problem after 50 years of investigation is still unsolved and needs to make further researches. Opinions of former socialistic and West countries authors are very different. It is important to determine indications for classification of cost accounting and product costing methods. Recommended classification indications: 1) according to the type of production Gob order, process); 2) according to the scale of including of expenses into cost (absorption, direct); 3) according to level of costs ratio (standard, nonstandard); 4) according to costing objects (products, activities, functions).Research of cost budgets formation displayed that lack of examples and methodical instructions for budget formation leads to problems in practice. It is recommended to form cost budgets as follows: 1) general cost budget, 2) cost budget of primary raw materials’ expenses, 3) cost budget of direct payroll expenses, 4) budget of production overheads, 5) budget of production unit costs, 6) adjustment of general cost budget.Conclusions regarding determination of cost centres and their efficiency have shown that cost centres should be determined within the rules: 1) corresponding criterion of cost calculation should be determined for each cost centre; 2) each cost centre should be independent sphere of responsibility; 3) all registered costs should be ascribed to corresponding cost centre without any difficulty. It is not permitted to identify the cost centres together with places of cost formation. Each cost centre consists of different places of cost formation and, in addition, it can include cost without exact place of formation.